Method for producing positive electrode active material

By controlling the sulfate ion concentration of the transition metal solution to be less than 0.9 mol/L, the problem of excessive sulfate mixing in the positive electrode active substance of the lithium-ion secondary battery is solved, which reduces the initial resistance and improves the battery performance.

CN119430313APending Publication Date: 2025-02-14PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411029161.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-07-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The amount of sulfate mixed in the positive electrode active substance of existing lithium-ion secondary batteries is too large, resulting in an increase in initial resistance and affecting battery performance.

Method used

By controlling the sulfate ion concentration of the transition metal solution to be less than 0.9 mol/L, the amount of sulfate mixed in the positive electrode active material is reduced, thereby reducing the initial resistance of the lithium-ion secondary battery.

Benefits of technology

It effectively reduces the amount of sulfate mixed in the positive electrode active substance, reduces the initial resistance of the lithium-ion secondary battery, and improves battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430313A_ABST
    Figure CN119430313A_ABST
Patent Text Reader

Abstract

The present disclosure can provide a method for manufacturing a positive electrode active material that can contribute to improving battery performance. The disclosed manufacturing method comprises: a preparation step (S10) in which a starting material containing at least a transition metal element is prepared; a preparation step (S20) for preparing a transition metal solution by dissolving the transition metal element in the starting material in the extraction solution; a precursor generation step (S30) in which the positive electrode active material precursor is crystallized by adding an alkali solution to the transition metal solution; and an active material generation step (S40) for generating a positive electrode active material by heating the positive electrode active material precursor together with a lithium compound. Furthermore, the disclosed production method is characterized in that the sulfate ion concentration of the transition metal solution when the precursor generation step is performed is 0.9 mol / L or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a positive electrode active material. Specifically, the technology disclosed herein relates to a method for producing a positive electrode active material for a lithium ion secondary battery. Background Art

[0002] Lithium ion secondary batteries are widely used in various devices such as mobile terminals and vehicles. Among the positive electrode active materials of the lithium ion secondary batteries, for example, lithium transition metal composite oxides are used. As transition metals contained in the lithium transition metal composite oxides, Ni, Co, Mn, etc. can be cited.

[0003] Patent document 1 discloses an example of a precursor of such a positive electrode active material (lithium transition metal composite oxide). As described in patent document 1, in the manufacture of a positive electrode active material, a sulfate of a transition metal (NiSO4, CoSO4, MnSO4, etc.) is usually prepared as a starting material. Next, a mixed aqueous solution (transition metal solution) in which the sulfate is dissolved in water is prepared. Then, an alkali solution (NaOH, etc.) is added to the transition metal solution. Thus, a compound containing a transition metal (positive electrode active material precursor) is precipitated. Then, the positive electrode active material precursor is mixed with a lithium compound and calcined. Thus, a lithium transition metal composite oxide can be generated.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2018 / 123995 Summary of the invention

[0007] However, in recent years, the performance requirements for lithium ion secondary batteries have further increased. The technology disclosed herein has been completed in response to the above requirements, and its purpose is to provide a method for producing a positive electrode active material that can contribute to improving battery performance.

[0008] In order to solve the above-mentioned problems, a method for producing a positive electrode active material having the following structure (hereinafter, also simply referred to as a “production method”) is provided.

[0009] The manufacturing method of the positive electrode active material disclosed herein includes the following steps: a preparation step, preparing a starting material containing at least a transition metal element; a preparation step, preparing a transition metal solution by dissolving the transition metal element in the starting material in an extract; a precursor generation step, crystallizing the positive electrode active material precursor by adding an alkaline solution to the transition metal solution; an active material generation step, generating the positive electrode active material by heating the positive electrode active material precursor with a lithium compound. Moreover, the manufacturing method disclosed herein is characterized in that the sulfate ion concentration of the transition metal solution during the precursor generation step is set to 0.9 mol / L or less.

[0010] As mentioned above, in the manufacture of general positive electrode active materials, transition metal sulfates (NiSO4, CoSO4, MnSO4, etc.) are used as starting materials. Therefore, sulfates such as sodium sulfate (Na2SO4) are sometimes mixed into the positive electrode active material after manufacture. Moreover, the research results of the present inventors show that if the amount of sulfate mixed into the positive electrode active material increases, the initial resistance of the lithium ion secondary battery increases. The manufacturing method disclosed herein is completed based on such insights. Specifically, the manufacturing method disclosed herein causes the sulfate ions (SO4 2- ) concentration is 0.9 mol / L or less. This can reduce the amount of sulfate mixed in the positive electrode active material after production, thus contributing to reducing the initial resistance of the lithium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a flowchart for explaining the method for producing the positive electrode active material according to the first embodiment.

[0012] Figure 2 This is a flowchart for explaining the preparation process in another embodiment. DETAILED DESCRIPTION

[0013] Hereinafter, the implementation methods of the technology disclosed herein will be described with reference to the accompanying drawings. It should be noted that matters other than those specifically mentioned in this specification and required for the implementation of the technology disclosed herein can be grasped as design matters for those skilled in the art based on the prior art in this field. The technology disclosed herein can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, the expression "A to B" indicating the range in this specification means above A and below B, and also includes the meanings of "preferably greater than A" and "preferably less than B".

[0014] <First embodiment>

[0015] Hereinafter, a first embodiment of the production method disclosed herein will be described. It should be noted that, below, after describing the positive electrode active material to be produced, the specific steps of the production method of this embodiment will be described.

[0016] [Positive electrode active material]

[0017] In the manufacturing method of the present embodiment, a lithium transition metal composite oxide used as a positive electrode active material for a lithium ion secondary battery is manufactured. The lithium transition metal composite oxide is an oxide containing lithium (Li) and a transition metal element. As the transition metal element here, nickel (Ni), cobalt (Co), manganese (Mn), etc. can be cited. As a specific example of the lithium transition metal composite oxide, lithium nickel composite oxide (LN oxide), lithium cobalt composite oxide (LC oxide), lithium nickel manganese composite oxide (LNM oxide), lithium manganese cobalt composite oxide (LMC oxide), lithium nickel cobalt composite oxide (LNC oxide), lithium nickel cobalt manganese composite oxide (LNCM oxide), etc. can be cited. It should be noted that these lithium transition metal composite oxides may also contain elements (additive elements) other than Li and transition metal elements. As the additive element, Mg, Ca, Al, Ti, V, Cr, Si, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, Sn, B, C, Si, P, S, F, Cl, Br, I, etc. can be cited.

[0018] The details will be described later. According to the manufacturing method of this embodiment, the amount of sulfate mixed in the positive electrode active material after manufacturing can be reduced. Specifically, according to the manufacturing method of this embodiment, the sulfate ion (SO4 2- ) content is reduced to 1.2wt% or less (preferably 0.9wt% or less, more preferably 0.6wt% or less, and particularly preferably 0.3wt% or less). This can reduce the initial resistance of the lithium-ion secondary battery. It should be noted that the "sulfate ion (SO4 2- ) content” is a value calculated based on the measurement results of high-frequency inductively coupled plasma (ICP: Inductively Coupled Plasma). Specifically, by using ICP, the weight (wt%) of sulfur element (S) in the positive electrode active material can be measured. In addition, if sulfate ions (SO4 2- ) composition, the content of sulfate ions can be calculated based on the weight of the above-mentioned sulfur element.

[0019] [Method for producing battery materials]

[0020] Next, a method for producing the positive electrode active material according to the present embodiment will be described. Figure 1This is a flowchart for explaining the method for producing the positive electrode active material according to the present embodiment.

[0021] like Figure 1 As shown, the method for producing a battery material of this embodiment includes a preparation step S10, a preparation step S20, a precursor production step S30, and an active material production step S40. Each step will be described below by taking the case of producing LNCM oxide as a positive electrode active material as an example.

[0022] (1) Preparation step S10

[0023] In the preparation process S10, a starting material containing at least a transition metal element is prepared. The details are described later, and the starting material can be appropriately selected from previously known raw materials according to the composition of the manufacturing target (positive electrode active material). For example, in the present embodiment, LNCM oxides containing Ni, Co and Mn as transition metal elements are manufactured. In this case, in this process, starting materials containing Ni, Co and Mn are prepared. It should be noted that the type of starting materials prepared in this process can be one or more. Specifically, one starting material that can supply all required transition metal elements can be prepared. In addition, a variety of starting materials can also be prepared, and the required transition metal elements can be supplied by a combination of the multiple starting materials. For example, in the present embodiment, a starting material (NiCo source) containing Ni and Co and a starting material (Mn source) containing Mn are separately prepared. Thus, Ni, Co and Mn required for the manufacture of LNCM oxides can be supplied. It should be noted that the NiCo source in the present embodiment is formed by calcining the positive electrode active material (LNCM oxide) of a used lithium-ion secondary battery. On the other hand, manganese chloride (MnCl 2 ) was used as the Mn source.

[0024] (2) Preparation process S20

[0025] In the preparation process S20, a transition metal solution is prepared by dissolving the transition metal element in the starting raw material in the extract. As long as this process can prepare a transition metal solution containing the desired transition metal element, the steps known in the past can be adopted without particular restrictions. In the present embodiment, the NiCo raw material (calcined LNCM oxide) is first immersed in ammonia water. Thus, the nickel oxide (NiO) and cobalt oxide (CoO) in the calcined LNCM oxide seep into the ammonia water. Thus, a solution (NiCo solution) containing Ni element and Co element can be obtained. On the other hand, manganese oxide (MnO) in the calcined LNCM oxide is difficult to seep into ammonia water. Therefore, in the present embodiment, manganese chloride is separately prepared as a Mn source. Then, by dissolving the manganese chloride in other extracts (water, etc.), a solution (Mn solution) containing the Mn element can be prepared. Then, by adding the Mn solution to the above-mentioned NiCo solution, a transition metal solution (NiCoMn solution) containing Ni, Co and Mn can be prepared.

[0026] It should be noted that the metal concentration of the transition metal solution is preferably 1.0 mol / L or more, more preferably 1.2 mol / L or more, further preferably 1.4 mol / L or more, and particularly preferably 1.5 mol / L or more. Thus, in the precursor generation step S30, the cathode active material precursor can be efficiently crystallized. On the other hand, if the metal concentration of the transition metal solution is too high, it is possible to precipitate the metal under a small temperature change due to approaching saturated solubility. From this point of view, the metal concentration of the transition metal solution is preferably less than 2.6 mol / L, more preferably less than 2.4 mol / L, further preferably less than 2.2 mol / L, and particularly preferably less than 2 mol / L. In addition, the mixing ratio of the transition metal elements (Ni, Co, Mn, etc.) in the transition metal solution is appropriately adjusted according to the composition of the cathode active material of the manufacturing target.

[0027] In addition, in this process, a reducing agent and a pH buffer may also be added to the extract. Thus, the Ni element and the Co element can be more easily extracted. It should be noted that as a reducing agent, a hydrogen peroxide solution or the like can be preferably used. As a pH buffer, ammonium sulfate or the like can be preferably used. It should be noted that when ammonium sulfate is used as a pH buffer, as described later, it is preferred to adjust the amount of the pH buffer so that the sulfate ion concentration of the transition metal solution is 0.9 mol / L or less.

[0028] (3) Precursor generation step S30

[0029] In the precursor generation step S30, the positive electrode active material precursor is crystallized by adding an alkaline solution to the transition metal solution. In this step, as long as the positive electrode active material precursor can be generated, the previously known crystallization treatment can be adopted without particular limitation. As the alkaline solution, for example, an aqueous solution of ammonia (NH3), an aqueous solution of sodium hydroxide (NaOH), an aqueous solution of potassium hydroxide (KOH), etc. can be cited. In the present embodiment, an aqueous NaOH solution is added to the above-mentioned transition metal solution (NiCoMn solution) to control the pH of the transition metal solution to be strongly alkaline (pH=11 or above). Thus, NiCoMn hydroxide is crystallized in the transition metal solution. The NiCoMn hydroxide can be collected by using solid-liquid separation. Then, the collected NiCoMn hydroxide is washed with water or the like and then dried. Thus, a dried NiCoMn hydroxide (positive electrode active material precursor) is obtained.

[0030] (4) Active Material Generation Step S40

[0031] In the active material generation step S40, the positive electrode active material is generated by heating the positive electrode active material precursor and the lithium compound together. In the present embodiment, the positive electrode active material precursor (NiCoMn hydroxide) is mixed with the lithium compound (Li2CO3, LiOH, etc.). It should be noted that the mixing ratio here is appropriately adjusted according to the composition of the positive electrode active material of the manufacturing target. Then, the mixture is calcined in an oxygen atmosphere. Thus, the positive electrode active material (LNCM oxide) of the lithium ion secondary battery can be manufactured.

[0032] It should be noted that the maximum temperature in the above calcination treatment is preferably 700°C or more, more preferably 725°C or more, further preferably 750°C or more, and particularly preferably 775°C or more. Thus, the positive electrode active material precursor is properly reacted with the lithium compound, and the positive electrode active material precursor can be efficiently generated. On the other hand, if the maximum temperature is too high, it may become the cause of the decline in battery characteristics due to excessive crystal growth. From this point of view, the maximum temperature in the calcination treatment is preferably 900°C or less, more preferably 875°C or less, further preferably 850°C or less, and particularly preferably 825°C or less. In addition, the calcination time is preferably 3 hours or more, more preferably 3.5 hours or more, further preferably 4 hours or more, and particularly preferably 4.5 hours or more. Thus, the positive electrode active material precursor can be fully reacted with the lithium compound. On the other hand, the upper limit of the calcination time is not particularly limited, and can be 7 hours or less, 6.5 hours or less, 6 hours or less, or 5.5 hours or less. It should be noted that the "calcination time" in this specification refers to the time for maintaining the maximum temperature.

[0033] (5) Control of sulfate ions

[0034] The manufacturing method disclosed herein is characterized in that the sulfate ion concentration of the transition metal solution during the precursor generation step is set to 0.9 mol / L or less. According to experiments conducted by the inventors, it has been confirmed that the use of such a transition metal solution with a low sulfate ion concentration can reduce the amount of sulfate mixed in the positive electrode active material after manufacturing. Moreover, by using the positive electrode active material, the initial resistance of the lithium ion secondary battery can be reduced.

[0035] Here, in the manufacturing method of the first embodiment, a starting material that is substantially free of sulfur is used. Thus, the sulfate ion concentration of the transition metal solution can be controlled to be less than 0.9 mol / L. Specifically, in the present embodiment, a used positive electrode active material (LNCM oxide) is used as a NiCo source. The used positive electrode active material is different from nickel sulfate (NiSO4) used as a Ni source in the past, cobalt sulfate (CoSO4) used as a Co source in the past, and substantially does not contain sulfur. In addition, manganese chloride used as a Mn source is also different from manganese sulfate (MnSO4) used as a Mn source in the past, and substantially does not contain sulfur. By using these starting materials, it is possible to prevent sulfur from being mixed in from the starting materials. Thus, the sulfate ion concentration of the transition metal solution can be controlled to be less than 0.9 mol / L. Moreover, if the transition metal solution is used, the amount of sulfate (Na2SO4, etc.) precipitated in the precursor generation step S30 can be greatly reduced. As a result, the amount of sulfate mixed in the positive electrode active material after manufacture can be reduced, and the performance (initial resistance) of the lithium ion secondary battery can be improved.

[0036] It should be noted that "using a starting material that does not substantially contain sulfur" in this specification means that a compound containing sulfur is not intentionally used as a starting material. Therefore, the case where sulfur is inevitably and slightly mixed into the starting material due to the manufacturing process, etc. is interpreted as "using a starting material that does not substantially contain sulfur." ​​For example, when the content of sulfur relative to the total weight (100wt%) of the starting material is 1wt% or less (preferably 0.1wt% or less, more preferably 0.01wt% or less, further preferably 0.001wt% or less, and particularly preferably 0.0001wt% or less), it can be said that "using a starting material that does not substantially contain sulfur." ​​If such a starting material is used, a transition metal solution having a sulfate ion concentration of 0.9 mol / L or less can be easily prepared.

[0037] In addition, the sulfate ion concentration of the transition metal solution is preferably 0.8mol / L or less, more preferably 0.7mol / L or less, further preferably 0.6mol / L or less, and particularly preferably 0.5mol / L or less. As the sulfate ion concentration of the transition metal solution decreases, the amount of sulfate mixed in the positive electrode active material decreases, so a higher performance positive electrode active material can be manufactured. On the other hand, the lower limit of the sulfate ion concentration of the transition metal solution is not particularly limited, and may also be 0mol / L (completely free of sulfate ions).

[0038] In addition, the total amount of transition metal elements in the transition metal solution (M T ) and the amount of sulfur element (M S ) ratio (M S / M T ) is preferably 0.5 or less, more preferably 0.3 or less, further preferably 0.1 or less, and particularly preferably 0.01 or less. Thus, the amount of sulfate precipitated simultaneously with the positive electrode active material precursor (transition metal hydroxide) can be further reduced. As a result, the amount of sulfate mixed in the positive electrode active material after manufacture can be more appropriately reduced. On the other hand, the above-mentioned M S / M T The lower limit of is not particularly limited and may be 0 or more (M S =0mol / L).

[0039] <Other embodiments>

[0040] The first embodiment of the technology disclosed herein has been described above. It should be noted that the technology disclosed herein is not limited to the first embodiment described above, and includes other embodiments after various configurations are changed. Other examples of the embodiments of the technology disclosed herein will be described below.

[0041] (1) Type of starting material

[0042] In the first embodiment, a used positive electrode active material (LNCM oxide) is used as a NiCo source. In addition, in the first embodiment, manganese chloride (MnCl2) is used as a Mn source. However, the manufacturing method disclosed herein is not limited to the use of a specific starting raw material. For example, as other examples of the starting raw material (Ni source) for supplying Ni, nickel oxide, nickel carbonate, nickel acetate, nickel chloride, nickel hydroxide, nickel nitrate, etc. can be used. In addition, as other examples of the starting raw material (Co source) for supplying Co, cobalt oxide, cobalt carbonate, cobalt acetate, cobalt chloride, cobalt hydroxide, cobalt nitrate, etc. can be used. In addition, as other examples of the starting raw material (Mn source) for supplying Mn, in addition to manganese chloride, manganese oxide, manganese carbonate, manganese acetate, manganese chloride, manganese hydroxide, manganese nitrate, etc. can also be used. Since these starting raw materials do not substantially contain sulfur element, it is possible to easily prepare a transition metal solution with a sulfate ion concentration of less than 0.9 mol / L.

[0043] In addition, the technology disclosed herein does not prohibit the use of sulfates (nickel sulfate, cobalt sulfate, manganese sulfate, etc.) as starting materials. In other words, as long as the sulfate ion concentration of the transition metal solution can be controlled to be below 0.9 mol / L, sulfates can also be used as part of the starting materials. For example, as long as a NiCo source (a used positive electrode active material, etc.) that does not substantially contain sulfur is used, the mixing of sulfur elements from the supply of Ni and Co can be suppressed. Moreover, in the case where the positive electrode active material of the manufacturing target is a low-Mn LNCM material, the amount of Mn source added is a small amount compared to the NiCo source. In this case, even if the Mn source uses sulfate (manganese sulfate), the sulfate ion concentration of the transition metal solution can be suppressed to below 0.9 mol / L.

[0044] (2) Selection of starting materials

[0045] In the above embodiment, the sulfate ion concentration of the transition metal solution is controlled to be less than 0.9 mol / L using a starting material with a clear composition. However, the manufacturing method disclosed herein may also use a material with an unknown composition (minerals collected, recycled materials with unknown origin, etc.) as a starting material. In this case, Figure 2 As shown, in the preparation step S10, the measurement step S12 and the raw material selection step S14 may be performed.

[0046] First, in the measurement step S12, the molar concentration of sulfur in the starting raw material is measured. In this step, the elemental analysis technology known in the past can be used without particular limitation. As an example of such an elemental analysis technology, ICP analysis, SEM-EDS analysis, XRF analysis, etc. can be cited. Next, in the raw material selection step S14, a starting raw material having a molar concentration of sulfur below a predetermined threshold is selected as the starting raw material for the preparation step S20. Thus, even when a starting raw material whose detailed composition is unknown is used, the sulfate ion concentration of the transition metal solution can be sufficiently reduced. It should be noted that the threshold value set in the raw material selection step S14 can be appropriately set from the perspective of suppressing the sulfate ion concentration of the transition metal solution to below 0.9 mol / L.

[0047] It should be explained that Figure 2 The measurement step S12 and the raw material selection step S14 shown can also be implemented when using a starting raw material with a clear composition. In this way, the amount of sulfur element mixed into the starting raw material in the form of impurities can be grasped, so the mixing of sulfur element from the starting raw material can be more appropriately suppressed. In addition, the above-mentioned measurement step S12 and the raw material selection step S14 do not need to be implemented for all the starting raw materials used. For example, the measurement step S12 and the raw material selection step S14 can be implemented when the type or batch of the starting raw material changes, when other process conditions are changed, etc. In this way, a positive electrode active material with a small amount of sulfate mixed in can be manufactured without significantly reducing the manufacturing efficiency.

[0048] (3) Type of extract

[0049] In the first embodiment, aqueous ammonia is used as an extracting solution for extracting Ni and Co from a NiCo raw material. Furthermore, water is used as an extracting solution for extracting Mn from a Mn raw material. However, the extracting solution used in the preparation process S20 can be selected from conventionally known extracting solutions without particular restrictions as long as it can extract the target transition metal element from the starting raw material. Other examples of the extracting solution include organic acids such as citric acid, ascorbic acid, oxalic acid, and acetic acid, and inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, and sulfuric acid. Among them, sulfuric acid can be the cause of the sulfur element being mixed into the transition metal solution. Therefore, when sulfuric acid is used as an extracting solution, it is necessary to appropriately adjust the concentration of sulfuric acid, the type of starting raw material, etc. so that the sulfate ion concentration of the transition metal solution is below 0.9 mol / L.

[0050] (4) Separation of sulfur

[0051] In addition, in each of the above-mentioned embodiments, the sulfate ion concentration of the transition metal solution is controlled to be less than 0.9 mol / L by suppressing the mixing of sulfur elements from the materials (starting raw materials, extracts) of the transition metal solution. However, in the technology disclosed herein, when the precursor generation step S30 is implemented, it is sufficient to control the sulfate ion concentration of the transition metal solution to be less than 0.9 mol / L. That is, in the preparation step S20, after preparing a transition metal solution having a sulfate ion concentration exceeding 0.9 mol / L, the sulfate ions are removed from the transition metal solution. Even in the case of adopting such a method, the sulfate ion concentration of the transition metal solution can be controlled to be less than 0.9 mol / L to manufacture a positive electrode active material with a small amount of sulfate mixed in. It should be noted that as a specific method for removing sulfate ions from a transition metal solution, calcium hydroxide can be added. Thus, sulfate ions can be removed in the form of calcium sulfate.

[0052] (5) Type of positive electrode active material

[0053] In each of the above-mentioned embodiments, lithium nickel cobalt manganese composite oxide is manufactured as a positive electrode active material. However, the technology disclosed herein is not limited to the type of positive electrode active material to be manufactured. That is, according to the manufacturing method disclosed herein, other lithium transition metal composite oxides (LN oxide, LC oxide, LNM oxide, LMC oxide, LNC oxide, etc.) can also be manufactured.

[0054] [Test example]

[0055] Hereinafter, test examples related to the technology disclosed herein will be described. It should be noted that the contents of the test examples described below are not intended to limit the technology disclosed herein.

[0056] 1. Sample Preparation

[0057] In this experiment, three types of positive electrode active materials having different production steps were prepared. The production steps of each example are described below.

[0058] (1)Example 1

[0059] In Example 1, a sulfate of a transition metal is prepared as a starting material. Specifically, nickel sulfate hexahydrate (NiSO4·6H2O) is prepared as a Ni source. In addition, cobalt sulfate heptahydrate (CoSO4·7H2O) is prepared as a Co source. Then, manganese sulfate pentahydrate (MnSO4·5H2O) is prepared as a Mn source.

[0060] Next, a transition metal solution is prepared by dissolving the above transition metal sulfate in water. At this time, the amount of the starting material added is adjusted so that the concentration of the transition metal element in the solution is 1.5 mol / L. In addition, the mixing ratio of the Ni source, the Co source, and the Mn source is adjusted to Ni:Co:Mn=8:1:1.

[0061] Next, prepare a reaction tank containing 0.5wt% NH3 water. Then, maintain the temperature of the reaction tank at 40°C, and continuously drip transition metal solution, 28wt% NH3 water, and 30wt% NaOH aqueous solution while stirring at 600rpm. Then, while adjusting the amount of NaOH aqueous solution added to keep the pH in the reaction tank at 11.4, continuously drip transition metal solution and NaOH aqueous solution for 6 hours. Then, the solid components precipitated in the reaction tank are recovered by solid-liquid separation. Then, the recovered solid components are washed with water twice and then dried. The NiCoMn hydroxide obtained as above is used as a positive electrode active material precursor.

[0062] Next, a mixed material is prepared by mixing the positive electrode active material precursor with lithium hydroxide (LiOH). At this time, the mixing ratio of each material is adjusted so that the molar ratio of lithium to the transition metal element reaches 1.06:1. Then, the mixed material is calcined. It should be noted that the calcination conditions set the maximum temperature to 800°C, the calcination time to 5 hours, and the calcination atmosphere to an oxygen atmosphere. Thus, LNCM oxide (positive electrode active material) is manufactured.

[0063] (2)Example 2

[0064] In Example 2, the used positive electrode active material (LNCM oxide, Ni:Co:Mn=8:1:1) is first calcined (calcination temperature: 650°C, calcination time: 5 hours, calcination atmosphere: oxygen atmosphere). Then, the calcined positive electrode active material is used as a NiCo source. The positive electrode active material is immersed in an NH3 solution to allow the NiCo in the positive electrode active material to seep out. It should be noted that the NH3 solution uses a mixed solution of 28wt% NH3, 0.5mol / L (NH4)2SO4 and 0.5mol / L H2O2. In addition, in the NH3 immersion treatment, the NH3 solution is maintained at a temperature of 80°C and stirred at 500rpm while being immersed for 8 hours. Then, the solid component is removed by solid-liquid separation, thereby obtaining a solution containing Ni and Co (NiCo solution). Next, manganese sulfate pentahydrate (MnSO4·5H2O) was added to the NiCo solution so that the total concentration of the transition metal elements was 1.5 mol / L. Thus, a transition metal solution containing Ni, Co and Mn was prepared. Then, in Example 2, the positive electrode active material precursor was crystallized from the transition metal solution according to the same steps as in Example 1, and then the positive electrode active material precursor was used to manufacture LNCM oxide (positive electrode active material).

[0065] (3)Example 3

[0066] In Example 3, LiNi composite oxide was used as the used positive electrode active material, and calcination treatment and NH3 seepage were performed under the same conditions as in Example 2. Thus, only Ni was extracted from the used positive electrode active material. Next, cobalt sulfate heptahydrate (CoSO4·7H2O) and manganese sulfate pentahydrate (MnSO4·5H2O) were added to the Ni solution to prepare a transition metal solution containing Ni, Co and Mn. Then, in Example 3, LNCM oxide (positive electrode active material) was manufactured according to the same steps as in Example 1.

[0067] 2. Evaluation test

[0068] (1) Determination of sulfur content

[0069] During the preparation of Examples 1 to 3, a portion of the transition metal solution was collected and the amount of sulfur was determined using ICP analysis. Then, the sulfate ion concentration (mol / L) of the transition metal solution was calculated based on the measurement results. In addition, in this experiment, the amount of sulfate in the manufactured LNCM oxide was also measured. In the determination of the amount of sulfate, a solution in which the LNCM oxide was dissolved in nitric acid was prepared. Then, the solution was subjected to ICP analysis to determine the amount of sulfur. Then, the sulfate ion concentration in the positive electrode active material was calculated based on the amount of sulfur in the measurement results. The results are shown in Table 1.

[0070] (2) Fabrication of lithium-ion secondary batteries

[0071] Next, a lithium-ion secondary battery is made using the positive electrode active materials of Examples 1 to 3. Here, first, the positive electrode active material, the conductive material (graphite), the binding material (polyvinylidene fluoride powder), and N-methyl-2-pyrrolidone (NMP) are mixed to prepare a positive electrode composite material slurry. It should be noted that for the mixing ratio of each raw material, the conductive material is set to 1 part by mass and the binding material is set to 0.9 parts by mass relative to the positive electrode active material (100 parts by mass). Next, the positive electrode composite material slurry is applied to both sides of the positive electrode collector (aluminum foil) and dried. Then, the dried coating is rolled with a calendering roller. Thus, a positive electrode having a positive electrode active material layer formed on both sides of the positive electrode collector is made.

[0072] Next, a negative electrode having a negative electrode active material layer formed on both sides of a negative electrode collector (copper foil) was prepared. A mixture of a negative electrode active material (graphite), a binder (styrene-butadiene rubber) and a thickener (carboxymethyl cellulose) was used as the negative electrode active material layer. It should be noted that the mixing ratio of the negative electrode active material, the binder and the thickener was set to 98:1:1. In addition, a porous film having a three-layer structure of PP / PE / PP was prepared as a separator. Then, a wound electrode body was prepared using the positive electrode, the negative electrode and the separator. Then, the electrode terminals were installed on the wound electrode body and housed in an aluminum battery case. Next, a non-aqueous electrolyte was injected into the battery case to prepare a lithium ion secondary battery for evaluation. It should be noted that in this test, as a non-aqueous electrolyte, an electrolyte obtained by adding 1.0 mol / L of LiPF6 to a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:4:3 was used.

[0073] (3) Evaluation of output characteristics

[0074] The above evaluation battery is charged to half of the initial capacity at a constant current of 0.5It under a temperature environment of 25°C. Then, after stopping charging and leaving it for 15 minutes, the voltage is measured when it is charged for 10 seconds at a constant current of 0.1It. Next, the amount of electricity charged for 10 seconds is discharged, and then the current value is changed to measure the voltage when charged for 10 seconds. Then, the amount of electricity charged for 10 seconds is discharged. Then, while measuring the voltage, the above charge and discharge cycle is repeated with a current value from 0.1It to 2It. Then, the initial resistance is determined based on the measured voltage and current values. The results are shown in Table 1. It should be noted that Table 1 shows the ratio when the initial resistance of Example 1 is set to 100%.

[0075] @surface@

[0076]

[0077] As shown in Table 1, it was confirmed that the sulfate ion concentration of the transition metal solution was reduced by using LNCM oxide as part of the starting material. Moreover, it was found that the amount of sulfate mixed in the positive electrode active material could be reduced by controlling the sulfate ion concentration of the transition metal solution to 0.9 mol / L or less. Moreover, as shown in Examples 2 and 3, it was confirmed that the positive electrode active material with a small amount of sulfate mixed could reduce the initial resistance of the lithium ion secondary battery by more than 5%.

[0078] The above is a detailed description of the technology disclosed herein, but these are only examples and do not limit the scope of the protection requested. The technology described in the scope of the protection requested includes various embodiments obtained by variously deforming and changing the specific examples illustrated above. That is, the technology disclosed herein includes the methods described in the following items 1 to 5.

[0079] <Project 1>

[0080] A method for producing a positive electrode active material, comprising:

[0081] a preparation step of preparing a starting material containing at least a transition metal element, and a preparation step of preparing a transition metal solution by dissolving the transition metal element in the starting material in an extract.

[0082] a precursor generation step of adding an alkaline solution to the transition metal solution to crystallize a positive electrode active material precursor, and

[0083] an active material generation step of generating a positive electrode active material by heating the positive electrode active material precursor and a lithium compound together;

[0084] The sulfate ion concentration of the transition metal solution during the precursor generation step is set to 0.9 mol / L or less.

[0085] <Project 2>

[0086] The method for producing a positive electrode active material according to item 1, wherein the starting material contains at least Ni and / or Co.

[0087] <Project 3>

[0088] The method for producing a positive electrode active material according to item 1 or 2, wherein the starting material is a positive electrode active material of a used lithium ion secondary battery.

[0089] <Item 4>

[0090] The method for producing a positive electrode active material according to any one of items 1 to 3, wherein the preparation step comprises:

[0091] a measuring step of measuring the molar concentration of sulfur in the starting material; and

[0092] The raw material selection step selects a starting raw material having a molar concentration of sulfur element below a predetermined threshold as a starting raw material to be provided to the preparation step.

[0093] <Item 5>

[0094] The method for producing a positive electrode active material according to any one of items 1 to 4, wherein the extract is at least one selected from ammonia water, citric acid, ascorbic acid, oxalic acid, acetic acid, nitric acid, hydrochloric acid, phosphoric acid, and sulfuric acid.

Claims

1. A method for producing a positive electrode active material, characterized in that: include: A preparation step of preparing a starting material containing at least a transition metal element, a preparation step of preparing a transition metal solution by dissolving the transition metal element in the starting material in an extract, a precursor generation step of adding an alkaline solution to the transition metal solution to crystallize a positive electrode active material precursor, and an active material generation step of generating a positive electrode active material by heating the positive electrode active material precursor and a lithium compound together; The sulfate ion concentration of the transition metal solution during the precursor generation step is set to 0.9 mol / L or less.

2. The method for producing a positive electrode active material according to claim 1, wherein: The starting material contains at least Ni and / or Co.

3. The method for producing a positive electrode active material according to claim 2, wherein: The starting material is a positive electrode active material of a used lithium-ion secondary battery.

4. The method for producing a positive electrode active material according to claim 1, wherein: The preparation process comprises: a determination step of determining the molar concentration of sulfur in the starting material, and The raw material selection step selects a starting raw material having a molar concentration of sulfur element lower than a predetermined threshold as a starting raw material to be provided to the preparation step.

5. The method for producing a positive electrode active material according to any one of claims 1 to 4, wherein: The extract is at least one selected from ammonia water, citric acid, ascorbic acid, oxalic acid, acetic acid, nitric acid, hydrochloric acid, phosphoric acid and sulfuric acid.

Citation Information

Patent Citations

  • Nonaqueous electrolyte positive electrode active material precursor

    WO2018123995A1